The Angiogenic Potential of DPSCs and SCAPs in an In Vivo Model of Dental Pulp Regeneration - Petra Hilkens; Annelies Bronckaers; Jessica Ratajczak; Pascal Gervois; Esther Wolfs; Ivo Lambrichts (Stem Cells International)
Adequate vascularization, a restricting factor for the survival of engineered tissues, is often promoted by the addition of stem cells or the appropriate angiogenic growth factors. In this study, human dental pulp stem cells (DPSCs) and stem cells from the apical papilla (SCAPs) were applied in an in vivo model of dental pulp regeneration in order to compare their regenerative potential and confirm their previously demonstrated paracrine angiogenic properties. 3D-printed hydroxyapatite scaffolds containing DPSCs and/or SCAPs were subcutaneously transplanted into immunocompromised mice. After twelve weeks, histological and ultrastructural analysis demonstrated the regeneration of vascularized pulp-like tissue as well as mineralized tissue formation in all stem cell constructs. Despite the secretion of vascular endothelial growth factor in vitro, the stem cell constructs did not display a higher vascularization rate in comparison to control conditions. Similar results were found after eight weeks, which suggests both osteogenic/odontogenic differentiation of the transplanted stem cells and the promotion of angiogenesis in this particular setting. In conclusion, this is the first study to demonstrate the successful formation of vascularized pulp-like tissue in 3D-printed scaffolds containing dental stem cells, emphasizing the promising role of this approach in dental tissue engineering.